Psychosocial adversities underestimated in hyperkinetic children - Overmeyer, Stephan; Taylor, Eric; Blanz, Bernhard; Schmidt, Martin H. (The journal of child psychology and psychiatry, 1999)
Abnormal psychosocial factors, assessed both clinically and by raters blind to clinical presentation, were examined in 21 hyperkinetic and 26 conduct disordered children. Blind raters found the frequency of psychosocial adversities to be similar in the two disorders. By contrast the clinical rater, who did know the diagnosis of patients, rated adverse psychosocial situations as much lower in hyperkinetic children than in children with conduct disorder. Logistic regression showed, particularly in the category of abnormal intrafamilial relationships (Lack of warmth in parent child relationship, Hostility or scapegoating of the child, Intrafamilial discord among adults), effects of the interaction between rater and knowledge of diagnosis. Clinical raters should be aware of abnormal psychosocial situations in hyperkinetic children and assess possible adverse effects on parents and children. Researchers should be aware of a possible bias in research interviews.